Procedures to Evaluate the Efficiency of Protective Clothing Worn by Operators Applying Pesticide - Espanhol-Soares, Melina; Nociti, Leticia A. S. [UNESP]; Machado-Neto, Joaquim Goncalves [UNESP] (Oxford University Press, 2013)
The evaluation of the efficiency of whole-body protective clothing against pesticides has already been carried out through field tests and procedures defined by international standards, but there is a need to determine the useful life of these garments to ensure worker safety. The aim of this article is to compare the procedures for evaluating efficiency of two whole-body protective garments, both new and previously used by applicators of herbicides, using a laboratory test with a mannequin and in the field with the operator. The evaluation of the efficiency of protective clothing used both quantitative and qualitative methodologies, leading to a proposal for classification according to efficiency, and determination of the useful life of protective clothing for use against pesticides, based on a quantitative assessment. The procedures used were in accordance with the standards of the modified American Society for Testing and Materials (ASTM) F 1359:2007 and International Organization for Standardization 174914. The protocol used in the field was World Health Organization Vector Biology and Control (VBC)/82.1. Clothing tested was personal water repellent and pesticide protective. Two varieties of fabric were tested: Beige (100% cotton) and Camouflaged (31% polyester and 69% cotton). The efficiency in exposure control of the personal protective clothing was measured before use and after 5, 10, 20, and 30 uses and washes under field conditions. Personal protective clothing was worn by workers in the field during the application of the herbicide glyphosate on weed species in mature sugar cane plantations using a knapsack sprayer. The modified ASTM 1359:2007 procedure was chosen as the most appropriate due to its greater repeatability (lower coefficient of variation). This procedure provides quantitative evaluation needed to determine the efficiency and useful life of individual protective clothing, not just at specific points of failure, but according to dermal protection as a whole. The qualitative assessment, which is suitable for verification of garment design and stitching flaws, does not aid in determining useful life, but does complement the quantitative evaluation. The proposed classification is appropriate and accurate for determining the useful life of personal protective clothing against pesticide materials relative to number of uses and washes after each use. For example, the Beige garment had a useful life of 30 uses and washes, while the Camouflaged garment had a useful life of 5 uses and washes. The quantitative evaluation aids in determining the efficiency and useful life of individual protective clothing according to dermal protection as a whole, not just at specific points of failure.
Keywords: ASTM 1359:2007; ISO 17491:2008; operator safety; property, plant, and equipment efficiency testing; tracer